ANALISIS LAPORAN KEUANGAN DENGAN METODE ALTMAN UNTUK MEMPREDIKSI KEPAILITAN PADA PERUSAHAAN INDUSTRI MAKANAN DAN MINUMAN - Santi Suci Rahayu; Rina Nofiyanti (Jurnal Ilmiah Ekonomi Bisnis, 2011)
Bankruptcy is a phenomenon which is avoided by any firms. For that we need a method that can be used as bankruptcy early warning systems. Altman method is one of the methods referred to. This study aimed to analyze financial statements using the Altman method and use the results of the analysis to predict the likelihood of bankruptcy of eleven food and beverage firms which are registered at the Indonesian Stock Exchange in the period 2003 to 2007. Data used in this research were secondary data obtained from financial statements (i.e., Income Statements and Balance Sheets) of 11 food and beverage firms. Altman method (Altman’s Z-score) was used to analyze data. The resulted Z-scores were used to predict the likelihood of bankruptcy at the studied firms. Results of the study showed that there are five firms in bankrupt category at least in one period; four firms in the category of potential bankruptcy (grey areas); at least in one period; and seven firms in healthy category at least in one period. Of the five firms which were included into bankruptcy category, only one was in the category for five consecutive years. There is no single firm for five consecutive years to be entered into the category of grey area. Of the seven firms that have been entered into healthy category, four firms are in healthy category for five consecutive years.